1989
DOI: 10.1164/ajrccm/140.5.1279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation of the Genioglossus on Upper Airway Resistance in Anesthetized Dogs

Abstract: We examined the relationship between the frequency of stimulation of the genioglossus and upper airway resistance in six anesthetized dogs in the supine position. The upper airway was isolated from the lower airway by transecting the cervical trachea, and the pressure flow relationship of the upper airway was obtained by applying constant negative pressure (5, 10, and 20 cm H2O) to the proximal cut end of the trachea. Electrical stimulation of the genioglossus was performed at a constant voltage (10 to 20 V) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 13 publications
2
36
0
2
Order By: Relevance
“…In anesthetized dogs and rabbits, these studies confirmed uniformly that UAW muscle con traction reduces Ruaw [7][8][9] and stabilizes the UAW against collapse [9][10][11]. In cats, however, both direct ES of the geniohyoid and HGN ES failed to reduce Ruaw [13.…”
Section: Hypoglossus Nerve Stimulationmentioning
confidence: 79%
“…In anesthetized dogs and rabbits, these studies confirmed uniformly that UAW muscle con traction reduces Ruaw [7][8][9] and stabilizes the UAW against collapse [9][10][11]. In cats, however, both direct ES of the geniohyoid and HGN ES failed to reduce Ruaw [13.…”
Section: Hypoglossus Nerve Stimulationmentioning
confidence: 79%
“…Considering the obvious role of neuromuscular mechanisms in the pathogenesis of OSA, since apnoeas occur only during sleep in association with a decline in GG activity [38], it is reasonable to assume that adequately applied electrical activation of this muscle may prevent pharyngeal collapse. Therefore, attempts to stimulate the GG in OSA patients for therapeutic purposes have been undertaken ever since the physiological importance of this muscles' action was appreciated, with variable results [2,36,39,40]. A major advance has been achieved recently when a group of OSA patients were implanted with chronic hypoglossus nerve stimulators, using cuff or sleeve-like electrodes implanted unilaterally around a hypoglossus nerve, with stimulation triggered by inspiration [3,41].…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 99%
“…The obvious need for new treatment modalities is directed towards two lines of approach: anatomic (such as surgical procedures) and functional, i.e. electrical stimulation of the upper airway dilator muscles [2,3]. The genioglossus (GG) muscle, which is the main tongue protrusor, has been shown to reduce pharyngeal resistance and collapsibility by far more than other upper airway dilator muscles [4,5], and has become, therefore, the main target for functional stimulation for therapeutic purposes [2,3].…”
mentioning
confidence: 99%
“…Electrical Stimulation for OSA Electrical stimulation of the hypoglossal nerve was first investigated in animal studies [80,81] to evaluate the role of the genioglossus muscle and the principal dilator muscle in maintaining upper airway patency during sleep. This review focuses on the results from the first chronic human study [82] using an implanted stimulation system (the Inspire I ™ system, Medtronic, Inc., USA).…”
Section: Oral Appliancesmentioning
confidence: 99%